Folhas tantas: o texto literário e a educação ambiental - Silva, Alessandra Cegobia de Andrade (2023)
This research has as its theme the literature associated with Environmental Education with students in the 2nd year of high school, at the Carlos Drummond de Andrade State School of Elementary and Secondary Education, in Rondônia. This study is developed through action research, with an exploratory and bibliographical approach; for data collection and qualitative purposes, a questionnaire with open and closed questions will be carried out. In relation to the corpus, the work focuses on the aesthetic production of indigenous literature authors Julie Dorrico (2019, 2020a, 2020b) and Márcia Kambeba (2020). In this way, we intend to demonstrate, through action research methodology, that reading literary texts by authors from the Amazon region can contribute to forming critical readers about the reality that surrounds them, sensitive to literary art and environmental awareness. This work has, as its research line, “Reading and Reader Training”, from the Postgraduate Program in Literature at the University of Passo Fundo (RS), and is based on the following theorists: Michèle Petit (2009, 2013, 2019), who addresses the role of reading in the formation of the individual (mainly in contexts of crisis or great social violence); Zygmunt Bauman (2001), who clarifies how the transition to modernity occurred, helping us to rethink the concepts and cognitive schemes used to describe the individual human experience; Rildo Cosson (2021), who proposes methods of reading practices on how to teach literature at school; Antonio Candido (2006), which focuses on various levels of the correlation between literature and society; Jorge Larrosa (2015), which takes a look at the relationships between human beings, their experiences and the world; and Ailton Krenak (2019, 2020), who contributes with reflections to deal with the main challenges that arise in the contemporary world. The action consisted of the development of four reading practices involving reading and writing texts, which allowed research participants to come into contact with indigenous literature with a focus on environmental themes, paving the way for the formation of literary readers — including in support of digital. It is in the school environment that the individual begins to be aware of their attitudes, so it is extremely important, currently, to work on environmental issues, seeking to enhance the participation of young people in complex activities in society, aspiring to the formation of active citizens, with environmental and social responsibility